Interplay of fear of God’s judgement and responsibility compulsion as nexus for encouraging responsible migration response - Christopher Magezi (Verbum et Ecclesia, 2019)
This article argues for the interplay of fear of God’s judgement and responsibility compulsion as a nexus for encouraging responsible migration response. This arises from the need of theology of migration that challenges the church to respond to migration challenges in a comprehensive manner. Given this, the aim of this article is to contribute migration theology that respond to the aforementioned proposed need. It utilises the available literature to establish the role of Israel in God’s redemptive history that includes her positive treatment of people from other nations, thereby also reminding the nations of what God expects of all people. In bringing the issue of the interplay of fear of God’s judgement and responsibility compulsion as a nexus for encouraging responsible migration response, it advances that God promises to judge and punish his people when they oppose his care and love for the vulnerable people such as aliens, widows and orphans (Ex 22:21–27). However, in remaining faithful to his aforementioned promises to the Israelites, God confronts them (the Israelites) in anger, judgement and punishment when they disobey him in the way they manage their relationship with people of other nations (Jr 7:1–15, 52; 2 Ki 24:10–20). With this in mind, it concludes by advancing the interplay of fear of God’s judgement and responsibility compulsion as nexus for encouraging responsible migration response within contemporary churches in South Africa and beyond.